2003
DOI: 10.1186/bcr587
|View full text |Cite
|
Sign up to set email alerts
|

Elevated mammaglobin (h-MAM) expression in breast cancer is associated with clinical and biological features defining a less aggressive tumour phenotype

Abstract: Background Mammaglobin ( h-MAM ) is expressed mainly by breast epithelial cells, and this feature has been used to detect circulating breast cancer cells and occult metastases in sentinel axillary lymph nodes of breast cancer patients. However, the biological role of mammaglobin is completely unknown. Methods We studied 128 fresh-frozen breast cancer specimens by means of reverse transcriptase–polymerase chain reaction and quantified their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 10 publications
8
42
0
1
Order By: Relevance
“…However, we detected an inverse association between mammaglobin mRNA expression in blood baseline samples and HER-2 overexpression or amplification in tumours. This is in contrast with the association of HER-2 overexpression and tumour aggressiveness [46] but in agreement with the reported lower expression of hMAM by breast tumour cells with a more aggressive phenotype documented by no expression of hormone receptors and high nuclear grade [19]. Thus, tumours with HER-2 overexpression may express lower or undetectable levels of hMAM transcript, which has not been studied before.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, we detected an inverse association between mammaglobin mRNA expression in blood baseline samples and HER-2 overexpression or amplification in tumours. This is in contrast with the association of HER-2 overexpression and tumour aggressiveness [46] but in agreement with the reported lower expression of hMAM by breast tumour cells with a more aggressive phenotype documented by no expression of hormone receptors and high nuclear grade [19]. Thus, tumours with HER-2 overexpression may express lower or undetectable levels of hMAM transcript, which has not been studied before.…”
Section: Discussionsupporting
confidence: 88%
“…If later samples were included in the analysis, up to 48 months, patients with at least one hMAM positive sample had better disease-free survival than patients who never had hMAM positive blood samples, contrary to the study hypothesis. Mammaglobin expression by breast cancer cells seems to be correlated with indicators of better prognosis [19]. This may explain why we observed that hMAM positivity in baseline peripheral blood samples was more frequent in patients with HER2-negative tumours than in patients harbouring tumors with HER2 overexpression/ amplification.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This over-expression did not appear to correlate with histology, tumor grade, tumor stage, or ER/PR status. A more recent study reported high MGB1 levels in primary breast cancers to be indicative of a less aggressive tumor phenotype and correlating with the expression of ER and PR, low Ki-67 labeling and absence of nodal invasion [133]. There has, so far, been no reported documentation of circulating transcripts of MGB1, however, MGB1 protein has been detected in sera of breast cancer patients [134,135].…”
Section: Human Mammaglobinmentioning
confidence: 99%